Narrativas (auto)biográficas e a formação matemática de pedagogos no contexto do Programa Institucional de Bolsa de Iniciação à Docência - PIBID: diálogos entrecruzados e pesquisa-formação - Marcondes, Luis Gustavo Rodrigues (2022)
This research, guided by the (auto)biographical approach, is concerned with the identification of marks in the professional teaching constitution resulting from processes of initial teacher education involving undergraduate students in Pedagogy at Universidade Federal de São Carlos - campus - Sorocaba, participants of the Institutional Program of Scholarship Incentive to Teaching (PIBID), inserted in a collaborative space of research-training focused on mathematics education that has as a reflection device the (auto)biographical writing. As a general objective, we seek to understand the marks provided by research-training spaces focused on Mathematics Education within the Institutional Program for Scholarship Initiation to Teaching, which have as a research device the (auto)biographical narratives within a collaborative process of initial training of early years' teachers. The methodology of data production is guided by the autobiographical and project workshops of Delory-Momberger (2006), the seminars and research and training groups proposed by Josso (2004) and the reflective groups discussed by Passeggi (2011). Data analysis and discussion took place in light of the concepts of interpretive-comprehensive analysis proposed by Souza (2014). The writings produced in the context of this research culminated in units of analysis that encompass cultural, social, and political aspects that drove relevant meanings for spaces of initial teacher education anchored in a collaborative movement. The observed marks show that the writing of the self as a training device contributes significantly to the construction of the teaching identity of educators in initial training and its relation to the teaching of mathematics. A collaborative space of formation allows these future professionals to redefine their lived experiences and thus, to move towards the awareness of a reflective, critical and meaningful teaching practice, having as a guide their life and training trajectories.